1997
DOI: 10.1099/00221287-143-8-2557
|View full text |Cite
|
Sign up to set email alerts
|

Association of newly discovered IS elements with the dichloromethane utilization genes of methylotrophic bacteria

Abstract: Dichloromethane (DCM) dehalogenases enable facultative methylotrophic bacteria t o utilize DCM as sole carbon and energy source. DCM-degrading aerobic methylotrophic bacteria expressing a type A DCM dehalogenase were previously shown to share a Conserved 4.2 kb BamHl DNA fragment containing the dehalogenase structural gene, dcmA, and dcmR, the gene encoding a putative regulatory protein. Sequence analysis of a 10 kb DNA fragment including this region led to the identification of three types of insertion sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…Within this genomic island, the dcm cluster contains three other genes, including the transcriptional regulator dcmR and two proteins of unknown function dcmB and dcmC and is flanked on both sides by IS1354 elements. This four-gene dcm islet is conserved within most DCM-degrading strains (18). However, a strain of M. extorquens DM4 with a deletion of the genomic island, known as DM4-2cr (20), requires only the dcmA gene to recover growth on DCM (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Within this genomic island, the dcm cluster contains three other genes, including the transcriptional regulator dcmR and two proteins of unknown function dcmB and dcmC and is flanked on both sides by IS1354 elements. This four-gene dcm islet is conserved within most DCM-degrading strains (18). However, a strain of M. extorquens DM4 with a deletion of the genomic island, known as DM4-2cr (20), requires only the dcmA gene to recover growth on DCM (21).…”
mentioning
confidence: 99%
“…Among several strains isolated for their ability to grow on DCM as the sole carbon and energy source (15,16), a strain of Methylobacterium extorquens known as DM4 has been investigated in the most detail. Through HGT, this strain has acquired a gene, dcmA, encoding a cytoplasmic glutathione S-transferase that converts DCM to formaldehyde, with the concomitant release of two molecules of hydrochloric acid (17,18). In M. extorquens DM4, the dcmA gene lies within a 126-kb genomic island that shows clear evidence of horizontal transfer, including a lower GC content (19).…”
mentioning
confidence: 99%
“…Among them, the best characterized are the haloalkane dehalogenase of Rhodococcus rhodochrous (28,46), the haloacetate dehalogenases of Xanthobacter autotrophicus (59) and Delftia acidovorans (53), and the dichloromethane dehalogenase in methylotrophic bacteria (49). More closely related to the numerous putative reductive dehalogenases of Dehalococcoides ethenogenes strain 195, a recent study revealed that the tetrachloroethene reductive dehalogenase genes (pceAB) of Desulfitobacterium hafniense strain TCE1 was embedded in a composite transposon, TnDha1, and that this transposon is probably also present in two other Desulfitobacterium strains.…”
Section: Discussionmentioning
confidence: 99%
“…DM11 from solvent-contaminated sludge, and methylotrophs DM6 and facultative DM5 isolated from various solvent-polluted soil. Few representatives of glutathione S-transferases are yet known in bacteria [4,5]. Only sequence data are available in most cases, although results with bacterial enzymes for which biochemical investigations have been carried out suggest enzymatic functions not usually observed in eukaryotic GST [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria, capable of growth with DCM as the sole source of carbon and energy under both aerobic and anaerobic conditions, have been isolated over the past two decades [4]. These include Hyphomicrobium sp DM2 and Methylobacterium sp DM4 isolated from groundwater, Methylophilus sp.…”
Section: Introductionmentioning
confidence: 99%